PENGARUH BAURAN PEMASARAN DAN CITRA MEREK TERHADAP MINAT BELI YANG DIMEDIASI OLEH EFEK PAMER PADA MOBIL LISTRIK WULING DI KUMALA MANADO - Mevander Mark Muntu; Bernard T Widjaja; Saparso; Sagai, Rilie Tirza Liliroyor (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study examines the influence of the marketing mix and brand image on purchase intention, with conspicuous consumption (Veblen Effect) as a mediating variable, in the case of Wuling electric vehicles (EVs) in Kumala Manado. The research is motivated by the growing competition in the automotive industry, particularly for new entrants such as Wuling Motors, and the unique consumer behavior in North Sulawesi, which emphasizes social status and prestige in purchasing decisions. Using a quantitative approach, the study surveyed 100 respondents to analyze the relationships between the variables. Structural Equation Modeling (SEM) with SmartPLS was employed to test the hypotheses. The results indicate that the marketing mix (product, price, place, and promotion) positively influences purchase intention both directly and through the Veblen Effect. Likewise, brand image significantly affects purchase intention and is also mediated by the Veblen Effect. The findings suggest that consumers in Manado are influenced not only by product attributes and brand perception but also by the desire to showcase social status through their purchases.